High Supersaturation in the Wake of Falling Hydrometeors: Implications for Cloud Invigoration and Ice Nucleation. Issue 10 (13th May 2020) - Prabhakaran, Prasanth; Kinney, Gregory; Cantrell, Will; Shaw, Raymond A.; Bodenschatz, Eberhard
Abstract: Aerosol particles, cloud droplets, and ice crystals, coupled through the supersaturation field, play an important role in the buoyancy and life cycle of convective clouds. This letter reports laboratory observations of copious cloud droplets and ice crystals formed in the wake of a warm, falling water drop, which is a laboratory surrogate for a relatively warm hydrometeor in atmospheric clouds, such as a graupel particle in the wet growth regime. Aerosols were activated in the regions of very high supersaturation due to mixing in the wake. A mechanism is explored for attaining very high supersaturations capable of activating significant fractions of the interstitial aerosols within the lifetime of a convective cloud. The latent heat released from the activation of interstitial aerosols and subsequent growth may provide an additional source of buoyancy for cloud invigoration and may lead to larger concentrations of ice crystals. Plain Language Summary: Hail or other large icy hydrometeors like graupel fall through clouds, leaving regions of disturbed turbulent air in their wake. Because graupel particles are very likely to be warm or cold, relative to their surroundings, numerous new cloud droplets and even ice crystals can form in the disturbed air. The heat associated with the condensation of water vapor onto these newly formed droplets or crystals could provide a significant boost to the cloud's buoyancy. Calculations suggest that this mechanism could expose regions of convective clouds to high supersaturations in tens of minutes, providing a source of invigoration and higher concentrations of ice crystals. Key Points: High supersaturation regions form in the wake of falling hydrometeors that are not in thermal equilibrium with the environment Nucleation of water droplets and ice crystals is observed in the wake of falling hydrometeors Secondary ice nucleation and convection invigoration due to the enhanced supersaturation in the wake of falling hydrometeors